Karakterisasi Morfologi Ikan Bujuk (Channa lucius) pada Perairan Danau Singkarak Sumatera Barat, Rawa Banjiran Tanjung Jabung Timur Jambi dan Rawa Banjiran Kampar Riau - Azrita, Azrita; Syandri, Hafrijal; Dahelmi, Dahelmi; Syaifullah, Syaifullah; Nugroho, Estu (Jurnal Natur Indonesia, 2013)
Overfishing, the use of unfriendly-environmental fishing gears, changes of environmental water conditions and diversity of habitats are threaten the continuity of Bujuk fish (Channa lucius) and generate the morphologycal diversity. Consequently, appropriate conservation efforts are needed to preserve the fish. The first phase of these efforts were done through morphological approach. The research was held in 2010 in Singkarak Lake West Sumatera Province, in floodplain, Pematang sub-district Lindung Mendahara Ulu Regency East Tanjung Jabung, Province of Jambi, and in floodplain Mentulik Regency Kampar Kiri Hilir Riau Province. The aims of the research were to analyze the morphological characteristic of the fish with Principal Component Analysis (PCA) and to determine the range of similarity between populations of the fish. Determination of the location of fish sampling was conducted by proposive sampling in which there were 30 samples for every research location. The measurement of the specimen was done by digital calipers on the left of the body, at 4 meristic characters and 19 morphometric characters. The data obtained were analyzed by One Way ANOVA and principal component analysis using Statistical software version 13. The results showed that based on the analysis of morphological characteristics of bujuk fish, populations that exist in Lake Singkarak were different from those of Pematang Lindung floodplain sub-district Mendahara Ulu Regency East Tanjung Jabung Jambi Province and Mentulik Regency floodplain Kampar Kiri Hilir Province Riau. The meristic difference was on the number of scales along the lateral line with a value of 0.783. While the main difference on morphometric characters were the snout length with a value of 0.848, and length of upper jaw with a value of 0.847. Thus, the study showed that the fish was isolated geographically into two groups, which were Jambi-Riau population and Singkarak Lake population.